Data-to-music sonification and user engagement - Middleton, Jonathan; Hakulinen, Jaakko; Tiitinen, Katariina; Hella, Juho; Keskinen, Tuuli; Huuskonen, Pertti; Culver, Jeffrey; Linna, Juhani; Turunen, Markku; Ziat, Mounia; Raisamo, Roope (Frontiers in Big Data, 2023)
The process of transforming data into sounds for auditory display provides unique user experiences and new perspectives for analyzing and interpreting data. A research study for data transformation to sounds based on musical elements, called data-to-music sonification, reveals how musical characteristics can serve analytical purposes with enhanced user engagement. An existing user engagement scale has been applied to measure engagement levels in three conditions within melodic, rhythmic, and chordal contexts. This article reports findings from a user engagement study with musical traits and states the benefits and challenges of using musical characteristics in sonifications. The results can guide the design of future sonifications of multivariable data.